Estudio Comparativo de Bioadsorción de Níquel en Aguas Sintéticas mediante Cáscaras de Toronja y Cebada - Álvarez Lema, Flavio Steven (2023)
The objective of this work is to evaluate and compare the bioadsorption efficiency of grapefruit peels and barley peels to separate nickel present in contaminated waters. Nickel contamination has serious consequences, since it is persistent, bioaccumulative and toxic for all living beings. This precept is the importance of exploring decontamination techniques for heavy metals in contaminated waters, one of them is bioadsorption, which is It is defined as a process that helps the active or passive uptake of metal ions. In the bioadsorption tests, a synthetic water solution of Nickel Sulfate hexahydrate (NiSO4. 6H2O) was considered, in two concentrations 100 ppm and 200 ppm. The parameters that are particle size of the bioadsorbent (300 µm and 600 µm), type of bioadsorbent (grapefruit peels and barley peels) and amount of bioadsorbent (1g, 1.5g, 2g and 3g) were taken into consideration. The methodology consisted of an analysis using an atomic absorption spectrophotometer (iCE 3000 SERIES AA Spectrophotometer). A total of 52 tests were developed and the main result was that the most effective bioadsorbent for adsorption of nickel present in synthetic water (100 ppm Ni) is grapefruit peel with a particle size of 600 µm, a quantity of 2 g and with a removal percentage of 82.63%. In the case of barley husk, the optimal result for the bioadsorption of nickel present in synthetic water (100 ppm Ni) was with a particle size of 300 µm, an amount of 3 g, having a removal percentage of 41.56%. These results demonstrate the bioadsorption capacity of the materials previously used in the treatment of water contaminated with nickel